Alternation Evaluation of the Cooperation Significance for Farmers Farm - Pečiuliauskas, Gintautas (Ekonomika, 2001)
The article deals with issues of alternation evaluation of the significance of cooperation for fanners farm in market economy. An integrated method is reccommended for this analysis. An estimation of alternation of number of cooperative enterprises and there members could be appropriate only when it assumes the changes of the total number of farmer at the same time. A common context of cooperation and its alternation have to be estimated as well. In this context , the process of specialisation of the farmer farms is considered as an important element. The advantages of the integrated method are demonstrated. The actual data on the evalution of cooperative enterprises in Denmark, France and Germany serves for reasoning the advantages. It is stated in the article, that the practice of fact-finding on cooperation and cooperative enterprises is not well-thought-out. It is proposed, that beside the data on the cooperative enterprises and their members, the data on the total number of farmers at the same period dealt with should be presented as well. On the basis of result analysis, the practical proporals for the development of cooperation in Lithuania are given. It is emphasized, that the farmers should associate into the numerous cooperative enterprises.